A rapid and efficient platform for antiviral crRNA screening using CRISPR-Cas13a-based nucleic acid detection - Yang, Lan; Zhang, Youcui; Yi, Wenyanbo; Dong, Xue; Niu, Mengwei; Song, Yingjie; Han, Yao; Li, Hao; Sun, Yansong (Frontiers in Immunology, 2023)
Rapid and high-throughput screening of antiviral clustered regularly interspaced short palindromic repeat (CRISPR) RNAs (crRNAs) is urgently required for the CRISPR-Cas13a antiviral system. Based on the same principle, we established an efficient screening platform for antiviral crRNA through CRISPR-Cas13a nucleic acid detection. In this study, crRNAs targeting PA, PB1, NP, and PB2 of the influenza A virus (H1N1) were screened using CRISPR-Cas13a nucleic acid detection, and their antiviral effects were confirmed. The results showed that crRNAs screened by CRISPR-Cas13a nucleic acid detection could effectively inhibit viral RNA in mammalian cells. Besides, we found that this platform for antiviral crRNA screening was more accurate than RNA secondary structure prediction. In addition, we validated the feasibility of the platform by screening crRNAs targeting NS of the influenza A virus (H1N1). Finally, this study provides a new approach for screening antiviral crRNAs and contributes to the rapid advancement of the CRISPR-Cas13a antiviral system.